1994
DOI: 10.1159/000168708
|View full text |Cite
|
Sign up to set email alerts
|

Fast Atom Bombardment Mass Spectrometric Determination of the Molecular Weight Range of Uremic Compounds that Displace Phenytoin from Protein Binding: Absence of Midmolecular Uremic Toxins

Abstract: Uremic compounds are known to displace phenytoin from protein binding, resulting in a higher concentration of the pharmacologically active free fraction of phenytoin. The true chemical identities and molecular weight range of all these compounds are still unknown. We demonstrated that indoxyl sulfate and hippuric acid, which are found at high concentrations in uremic patients, can only partially explain the elevated free phenytoin concentration. Other known uremic compounds, guanidine, methylguanidine, and gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…On the other hand, clinical factors such as renal function and co-medications were not found to be significant covariates in this dataset. Uremic toxins accumulated in end-stage renal disease may alter protein binding [63,64] and reduce the intrinsic clearance of phenytoin [65]; however, renal function (measured by SCr) was not identified as a significant covariate in this study, possibly because only a small number of patients had severe renal disease (i.e., GFR < 30 mL/min/1.73 m 2 ). Furthermore, concomitant low-dose aspirin did not impact phenytoin binding in this study, presumably because aspirin's effect is only evident at relatively higher doses [66].…”
Section: Discussionmentioning
confidence: 59%
“…On the other hand, clinical factors such as renal function and co-medications were not found to be significant covariates in this dataset. Uremic toxins accumulated in end-stage renal disease may alter protein binding [63,64] and reduce the intrinsic clearance of phenytoin [65]; however, renal function (measured by SCr) was not identified as a significant covariate in this study, possibly because only a small number of patients had severe renal disease (i.e., GFR < 30 mL/min/1.73 m 2 ). Furthermore, concomitant low-dose aspirin did not impact phenytoin binding in this study, presumably because aspirin's effect is only evident at relatively higher doses [66].…”
Section: Discussionmentioning
confidence: 59%
“…In uremia, the free fraction of phenytoin can be as high as 30%; in normal volunteers the free fraction is usually 10%. Another study indicated that several endogenous compounds with low molecular weights (less than 500 Da) play signifi cant roles in the displacement of strongly protein -bound drugs, but mid -molecular uremic toxins do not displace drugs (39) . Signifi cantly elevated free fractions of highly protein -bound anticonvulsants in uremia can only be partially explained by hypoalbuminemia.…”
Section: Monitoring Free Anticonvulsant Concentrations Patients With mentioning
confidence: 99%